2017
DOI: 10.3389/fpsyt.2017.00032
|View full text |Cite
|
Sign up to set email alerts
|

Depression Outcomes in Adults Attending Family Practice Were Not Improved by Screening, Stepped-Care, or Online CBT during a 12-Week Study when Compared to Controls in a Randomized Trial

Abstract: There is uncertainty regarding possible benefits of screening for depression in family practice, as well as the most effective treatment approach when depression is identified. Here, we examined whether screening patients for depression in primary care, and then treating them with different modalities, was better than treatment-as-usual (TAU) alone. Screening was carried out for depression using the 9-item Patient Health Questionnaire (PHQ-9), with a score of ≥10 indicating significant depressive symptoms. PHQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 59 publications
0
16
0
1
Order By: Relevance
“…1). Finally, we included 14 relevant RCTs comparing 33 treatments in 4183 participants (Hallgren et al, 2016;Kivi et al, 2014;Hoifodt et al, 2013;Levesque et al, 2011;Moreno et al, 2012;Montero-Marin et al, 2016;Nordgren et al, 2014;Simon et al, 2011;Silverstone et al, 2017;Salisbury et al, 2016;Gilbody et al, 2015;Hilty et al, 2007;Kessler et al, 2009;Burton et al, 2016).…”
Section: Trial Selectionmentioning
confidence: 99%
“…1). Finally, we included 14 relevant RCTs comparing 33 treatments in 4183 participants (Hallgren et al, 2016;Kivi et al, 2014;Hoifodt et al, 2013;Levesque et al, 2011;Moreno et al, 2012;Montero-Marin et al, 2016;Nordgren et al, 2014;Simon et al, 2011;Silverstone et al, 2017;Salisbury et al, 2016;Gilbody et al, 2015;Hilty et al, 2007;Kessler et al, 2009;Burton et al, 2016).…”
Section: Trial Selectionmentioning
confidence: 99%
“…A second systematic review [67] found that quality improvement programs, where screening was an integral part of the management, led to a reduction in depression scores. However, a recent study, where patients were randomized to screening with the PHQ-9 to guide management, concluded that screening had no impact on outcome after 12 weeks [68].…”
Section: Expectations On Instrumentsmentioning
confidence: 99%
“…Our findings are relevant from a cost-efficacy perspective, because if patients are properly assessed at the beginning, they can be promptly assigned to the most suitable therapeutic modality, thus saving unnecessary care costs and multiple futile efforts (Meeuwissen et al, 2019). In stepped care models, low-intensity treatment is recommended for all patients, and those who do not improve in the first step are referred to a high-intensity treatment (Bower & Gilbody, 2005;Silverstone et al, 2017; The National Institute for Health and Care Excellence -NICE, 2018). The results of this approach are likely to improve if patients who will not benefit from the low-intensity treatment, but may benefit from the high-intensity modality, can be identified at baseline (Lorenzo-Luaces, DeRubeis, van Straten, & Tiemens, 2017).…”
Section: Discussionmentioning
confidence: 99%